High Frequency Repetitive Transcranial Magnetic Stimulation Alleviates Cognitive Impairment and Modulates Hippocampal Synaptic Structural Plasticity in Aged Mice - Ma, Qinying; Geng, Yuan; Wang, Hua-long; Han, Bing; Wang, Yan-yong; Li, Xiao-li; Wang, Lin; Wang, Ming-wei (Frontiers in Aging Neuroscience, 2019)
Normal aging is accompanied by hippocampus-dependent cognitive impairment and act as a risk factor of Alzheimer’s disease (AD). The study aims to investigate the effect of high frequency repetitive transcranial magnetic stimulation (HF-rTMS) on hippocampus-dependent learning and memory in aged mice and to explore the underlying mechanisms. Forty-five male Kunming mice (15-month-old) were randomly divided into 3 aged groups: aged sham, 5Hz rTMS and 25Hz rTMS group. Two sessions of 5Hz or 25Hz rTMS comprising of 1000 pulses in 10 trains were delivered once a day for consecutive 14 days. Aged sham group were treated by the reverse side of the coil. In adult sham group, fifteen male Kunming mice (3-month-old) were treated the same way as aged sham group. Morris water maze (MWM) was conducted following the stimulation. The synaptic ultrastructure was observed by transmission electron microscope (TEM). HF-rTMS improved the spatial learning and memory impairment in aged mice and 5Hz was more significant than 25Hz. Synaptic plasticity associated gene profiles were modified by HF-rTMS, especially neurotrophin signaling pathway and cyclic adenosine monophosphate response element binding protein (CREB) cofactors. Compared to aged sham group Synaptic plasticity associated proteins, i.e. synaptophysin (SYN) and post synaptic density (PSD) 95 were increased, brain derived neurotrophic factor (BDNF) and phosphorylated CREB (pCERB) were significantly increased after 5Hz HF-rTMS treatment. Collectively, our results suggest that HF-rTMS ameliorated the cognitive deficits in natural aged mice. 5Hz rTMS treatment significantly enhances synaptic structural plasticity and actives BDNF / CREB pathway in hippocampus. Therefore, HF-rTMS may serve as an effective noninvasive, nonsurgical method for enhancing cognitive functions and may translate into novel treatments to alleviate cognitive decline in normal aging in the future.